Multiply and ull find ur answer
Answer:
c = -13.78.
Step-by-step explanation:
21.2x + c ≡ 5.3(4x - 2.6)
21.2x + c ≡ 21.2x - 13.78
Equating constant terms:
c = -13.78.
Answer:
1/6
Step-by-step explanation:
-3/4 - (-1/2) = - 1/4
-2/3 - 5/6 = - 3/2
-1/4 ÷ -3/2
3.141562.... And it goes on and on and on
Answer:
Step-by-step explanation:
In a geometric series, the successive terms differ by a common ratio which is determined by dividing a term by the preceding term.
The formula for determining the nth term of a geometric progression is expressed as
Tn = ar^(n - 1)
Where
a represents the first term of the sequence.
r represents the common ratio between successive terms in the sequence.
n represents the number of terms in the sequence.
From the seies shown,
a = 28
r = 98/28 = 343/98 = 3.5
The formula representing the nth term of the given sequence would be expressed as
Tn = 28 × (3.5)^(n - 1)